2018
DOI: 10.1002/cam4.1868
|View full text |Cite
|
Sign up to set email alerts
|

Pathological tumor infiltrative pattern and sites of initial recurrence in stage II/III gastric cancer: Propensity score matching analysis of a multi‐institutional dataset

Abstract: BackgroundAdvanced gastric cancer frequently recurs even after radical resection followed by adjuvant chemotherapy. The aim of this study was to evaluate the relationship between pathological infiltrative pattern (INF) and initial recurrence patterns in patients with stage II/III gastric cancer using a large multicenter database.MethodsWe retrospectively analyzed 1098 eligible patients who underwent curative gastrectomy for stage II/III gastric cancer at nine institutions between 2010 and 2014. Patients were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…We analyzed an updated multi‐institutional retrospective database compiled by integrating clinical data from nine institutions and performed a retrospective review of the clinical data for 3575 patients who underwent gastrectomy for gastric cancer between January 2010 and December 2014 . The eligibility criteria of this study included histologically proven adenocarcinoma, no preoperative treatment, and no residual lesions after surgery (Figure A).…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed an updated multi‐institutional retrospective database compiled by integrating clinical data from nine institutions and performed a retrospective review of the clinical data for 3575 patients who underwent gastrectomy for gastric cancer between January 2010 and December 2014 . The eligibility criteria of this study included histologically proven adenocarcinoma, no preoperative treatment, and no residual lesions after surgery (Figure A).…”
Section: Methodsmentioning
confidence: 99%
“…At present radical gastrectomy is regarded as the only approach to curing gastric cancer. However, about 30% of patients with gastric cancer have recurrence after receiving radical gastrectomy [ 4 , 5 ]. Thus it is difficult to achieve a cure for gastric cancer through surgery alone.…”
Section: Introductionmentioning
confidence: 99%
“…HNRNPK served as a target for miR-873-5p in XGC-1 cells. 5. The study provided a new mechanism to understand the progression of in ltrative GC.…”
mentioning
confidence: 94%
“…Moreover, the prognosis of in ltrative GC is worse than that of expanding GC [3]. Studies have reported that the recurrence of the peritoneal or liver after radical resection of GC is closely related to the pathological in ltrative pattern (INF) [4,5]. Therefore, it is of great signi cance to explore the latent molecular mechanism of in ltrative GC progression.…”
Section: Introductionmentioning
confidence: 99%